CRISPR Technology- A New Horizon in Clinical Dentistry- A Review (Bangladesh Journal of Medical Science, 2023)
Clustered Regularly InterSpaced Palindromic Repeats is known as CRISPR. It is a protein that can be programmed to change, eliminate, or activate the genome. This cutting-edge technology offers a broad range of possible implementation and is poised to revolutionise oral healthcare in the years to come. The most widely utilised genome editing techniques include homing endonucleases, Transcription Activator-Like Effector Nucleases, Zinc-Finger Nucleases, and CRISPR- CRISPR-associated protein 9 (Cas9). These adaptable genome-editing tools can alter the genomes in ways that are sequence-specific. Because it is highly effective and accurate, the genome editing method CRISPR-Cas9 has drawn attention as a potent weapon in the fight against cancer. This method and its uses, particularly in dental field, are covered in this review.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.42-46